2017
DOI: 10.1002/pri.1699
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of stabilising exercises in pelvic girdle pain during pregnancy and after delivery: A systematic review

Abstract: Background: Pelvic girdle pain is a common musculoskeletal disorder which affects women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 50 publications
1
28
0
2
Order By: Relevance
“…22 In 2017, Almousa and colleagues published a systematic review on the effectiveness of stabilizing exercises in pelvic girdle pain during pregnancy and after delivery. 23 Of 28 studies, only 6 fulfilled eligibility criteria (all 6 were RCTs) and only 2 studies showed that these types of exercises improve pain and quality of life. In the same year, a systematic review on the effectiveness of physical therapy in women with provoked vestibular pain was published by Morin and colleagues.…”
Section: Therapies For Pelvic Musculoskeletal Disordersmentioning
confidence: 99%
“…22 In 2017, Almousa and colleagues published a systematic review on the effectiveness of stabilizing exercises in pelvic girdle pain during pregnancy and after delivery. 23 Of 28 studies, only 6 fulfilled eligibility criteria (all 6 were RCTs) and only 2 studies showed that these types of exercises improve pain and quality of life. In the same year, a systematic review on the effectiveness of physical therapy in women with provoked vestibular pain was published by Morin and colleagues.…”
Section: Therapies For Pelvic Musculoskeletal Disordersmentioning
confidence: 99%
“…Although there has been growing interest among researchers regarding pelvic girdle pain after giving birth, the empirical evidence on this topic is still limited (Bjelland et al, 2013). For example, Stuge et al (2004) found that stabilizing exercises and physiotherapy improve pelvic girdle pain and disability two years after giving birth; overall, however, evidence on the effect of exercise and physiotherapy is disputed (Almousa, Lamprianidou, & Kitsoulis, 2018). Further, research focused on life with long-term pelvic girdle pain-for example exploring women's experiences of living with this condition and how they cope in their daily life-is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,8,10 Sin embargo, existen pocos estudios que determinen el número de repeticiones y la frecuencia necesaria para producir un efecto adecuado y duradero para el control del dolor. 11,12,13,14 Por esta razón, este estudio pretende valorar un programa específico de ejercicios de estabilización lumbopélvica que mejoren la flexibilidad y fuerza del centro del cuerpo (core) para que se reduzca la sintomatología dolorosa a nivel lumbar. Así, se evaluaron los efectos en la fuerza abdominal, el peso, el perímetro abdominal, la distancia dedos-piso y la escala de incapacidad por dolor lumbar de Oswestry -un cuestionario específico para dolor lumbar que mide las limitaciones que el dolor produce en las actividades cotidianas-.…”
Section: Introductionunclassified